Curricular Project in Santa Catarina, Brazil: historical-political approach on its development - Wanderléa Damásio Maurício; José Raul Staub; Juares da Silva Thiesen (Universidade Estadual Paulista Júlio de Mesquita Filho, 2011)
The article presents the first results of a research which analyzes the scholastic implications resulting from the implementation of the Curricular Project in the public school system of Santa Catarina - a study in progress at the Center of Education of the Federal University of Santa Catarina - UFSC. In the text, developed through an exploratory work, the authors describe and analyze the historical-political development of the Curricular Project in its first stage of discussion and systematization, in the late 80's and early 90's. To be able to accomplish this theoretical task, the work done identifies aspects of the relationship between the social and political context in Brazil and the scholastic movement of Santa Catarina which originated the formulation of the Curricular Project and highlights the implications of curricular thought that, in the 80's and 90's applied its hegemony on the discussions of this field in the country. In this article, the first conclusions of this stage of the research are presented, among which the following deserve special attention: a) the motivation which generated the formulation of the Curricular Project had a strong relationship with the Brazilian social and political reality in the late 80's;b) the formulation of the Project was not included as a topic for discussion in the syndical movements of that time - it happened due to the initiative taken by the Secretaria de Estado da Educação (State Office of Education); c) even though the authors of the Project made a choice for a well defined theoretical conception, there was no deepening about the field of curricular theory. The arguments presented in the text are supported by the literature, in official documents, and even in the books that constitute the Project themselves.